Primary gastric inflammatory myofibroblastic tumor treated with non‐exposed endoscopic wall‐inversion surgery (NEWS): A case report and literature review - Yuka Masuda; Yoshikazu Kanazawa; Osamu Goto; Daisuke Kakinuma; Kazutoshi Higuchi; Eriko Koizumi; Ryosuke Nakata; Nobuyuki Sakurazawa; Fumihiko Ando; Mikito Suzuki; Toshiro Yoshiyuki; Shunji Kato; et al. (DEN Open)
Abstract Inflammatory myofibroblastic tumor (IMT) is an intermediate malignancy with myofibroblast proliferation and inflammatory cell infiltration with malignant potential. Primary IMTs are predominantly reported in the lungs, while gastric IMTs are very rare. Therefore, no guidelines exist for the diagnosis and treatment of gastric IMTs. The present case is a 39‐year‐old man diagnosed with an asymptomatic gastric submucosal tumor. Considering the malignancy of the tumor, we selected non‐exposed endoscopic wall‐inversion surgery as the resection method and successfully performed local resection. Histopathological analysis showed myofibroblast proliferation and inflammatory cell infiltration, with a diagnosis of primary gastric IMT and negative resection margins. Immunohistochemical staining was negative for anaplastic lymphoma kinase. To the best of our knowledge, including our case, there have been 52 reported cases of primary gastric IMTs that have been treated, with several recurrent cases. In this study, we report the first case of local resection of gastric IMT using non‐exposed endoscopic wall‐inversion surgery, with a literature review.